2017
DOI: 10.1038/s41598-017-15220-z
|View full text |Cite
|
Sign up to set email alerts
|

Captive bottlenose dolphins and killer whales harbor a species-specific skin microbiota that varies among individuals

Abstract: Marine animals surfaces host diverse microbial communities, which play major roles for host’s health. Most inventories of marine animal surface microbiota have focused on corals and fishes, while cetaceans remain overlooked. The few studies focused on wild cetaceans, making difficult to distinguish intrinsic inter- and/or intraspecific variability in skin microbiota from environmental effects. We used high-throughput sequencing to assess the skin microbiota from 4 body zones of 8 bottlenose dolphins (Tursiops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 71 publications
8
50
0
Order By: Relevance
“…In addition, it underscores that although killer whale skin is influenced by the local environment (Romano‐Bertrand, Licznar‐Fajardo, Parer, & Jumas‐Bilak, ), it represents a unique ecosystem that is separate from that of the surrounding habitat. Concordant with our results, a study of the microbiome of four captive killer whales and the sea water from their pool found that the skin microbiota were more diverse and phylogenetically distinct from the sea water microbial community (Chiarello et al., ). Killer whales are highly social mammals (Baird, ; Ford, ), and thus, they are likely to have a high potential for horizontal transfer of microbes between individuals during contact (Nelson et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, it underscores that although killer whale skin is influenced by the local environment (Romano‐Bertrand, Licznar‐Fajardo, Parer, & Jumas‐Bilak, ), it represents a unique ecosystem that is separate from that of the surrounding habitat. Concordant with our results, a study of the microbiome of four captive killer whales and the sea water from their pool found that the skin microbiota were more diverse and phylogenetically distinct from the sea water microbial community (Chiarello et al., ). Killer whales are highly social mammals (Baird, ; Ford, ), and thus, they are likely to have a high potential for horizontal transfer of microbes between individuals during contact (Nelson et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…DNA was extracted from epidermal biopsies collected by firing a lightweight dart with a sterilized stainless steel cutting tip from a sterilized projector (e.g., Barrett-Lennard, Smith, & Ellis, 1996;Palsbøll, Larsen, & Hansen, 1991) at the flank of the killer whale. As a study on captive killer whales found low variability in the taxonomic composition of the skin microbiome from different body sites (Chiarello, Villéger, Bouvier, Auguet, & Bouvier, 2017), small variation in the exact location on the flank from which the biopsy was taken should not bias our results. Biopsies were stored in sterile tubes at −20°C.…”
Section: Sample Collection and Data Generationmentioning
confidence: 79%
See 3 more Smart Citations